Response of circulating fatty acid binding protein 4 concentration to low-intensity acute aerobic exercise is amplified in an exercise duration-dependent manner in healthy men - Shigeharu Numao; Ryota Uchida; Masaki Nakagaichi (Journal of Physiological Anthropology)
Abstract Background Circulating fatty acid-binding protein 4 (FABP4) influences cardiovascular disease and glucose metabolism. Acute aerobic exercise increases circulating FABP4 concentrations, but the factors underlying this effect in humans are unclear. We investigated the effect of exercise duration on circulating FABP4 concentrations in healthy men. Methods This randomized crossover study enrolled healthy young men randomly assigned to two trials, short-duration (SE) and long-duration (LE) aerobic exercises trials. Both involved acute aerobic exercise followed by 60 min of bed rest. The exercise intensity was the same (40% peak oxygen uptake); however, the duration was 40 and 70 min for the SE and LE trials, respectively. Venous blood samples were collected to measure hormones, metabolites, and FABP4 concentrations. Results Twelve healthy young men completed both trials. Changes in hormone levels did not differ significantly between the SE and LE trials (p > 0.05). However, the circulating FABP4 concentration increased significantly only in the LE trial immediately after exercise (p = 0.018). It increased significantly 30–60 min post-exercise in both the SE and LE trials (p < 0.018), with the extent of the increase being significantly higher in the LE trial than in the SE trial (p < 0.001). In each trial, the total incremental area under the curve of circulating FABP4 concentration was significantly positively correlated with body fat percentage (SE trial: r s = 0.699, p = 0.019; LE trial: r s = 0.643, p = 0.024). Conclusion Our findings suggest that exercise duration is associated with the magnitude of increased FABP4 secretion into the blood circulation. Body fat accumulation may also be involved in the magnitude of FABP4 secretion induced by acute aerobic exercise. Trial registration The study was pre-registered with the University Hospital Medical Information Network Center (UMIN), a clinical trial registration system (ID: UMIN000051068).